Classification of Breast Cancer Images by Using of Convolutional Attribute of ANN - Ozyurt, Fatih; Togacar, Mesut; Avci, Engin; Avci, Derya (Ieee, 2018)
Classic classiification methods needs expert knowledge and time. Deep learning methods do not need expert knowledge. Therefore in this paper deep learning methods had been used for classification of breast cancer.
3rd International Conference on Computer Science and Engineering (UBMK) -- SEP 20-23, 2018 -- Sarajevo, BOSNIA & HERCEG
Keywords: Deep learning; ANN; Classification; Breast calmer